Which pancreaticoduodenectomy dunking conduit is optimal for very small pancreatic ducts? - Patricia C. Conroy; Alexa Glencer; Sarah Mohamedaly; Lucia Calthorpe; Joseph Lin; Fernanda Romero-Hernandez; Kenzo Hirose; Eric Nakakura; Carlos Corvera; Kimberly S. Kirkwood; Ajay V. Maker; Adnan Alseidi; et al. (Clinical Surgical Oncology)
Background: Pancreaticoduodenectomy data regarding the optimal technique for reconstruction of small pancreatic ducts, where duct-to-mucosa is technically difficult, are lacking. We sought to retrospectively evaluate outcomes of dunking pancreaticojejunostomy (DPJ) compared to dunking pancreaticogastrostomy (DPG) after pancreaticoduodenectomy. Methods: Using NSQIP-targeted pancreatectomy data (2014–2019), we retrospectively identified patients undergoing elective pancreaticoduodenectomy with small pancreatic ducts (<3 ​mm) who underwent DPJ or DPG. Outcomes between patients undergoing DPJ versus DPG were compared using multivariable regression. Results: Among 780 patients, 79.8% underwent DPJ and 20.1% DPG. Patient comorbidities were similar. More patients who underwent DPG were Black, underwent vascular reconstruction (29.0% v. 10.5%; p ​< ​0.001), and had shorter operative time (324 v. 377 ​min; p ​< ​0.001). After adjustment, DPJ reconstruction was associated with higher likelihood of clinically-relevant postoperative pancreatic fistula (CR-POPF) (OR 2.1; p ​= ​0.024), deep abscess (OR 1.9; p ​= ​0.041), and postoperative percutaneous drainage (OR 2.2; p ​= ​0.027). There was no difference in delayed gastric emptying, postoperative sepsis, transfusions, reoperation, length of stay, or 30-day readmission. Conclusion: Among patients with small pancreatic ducts where a dunking pancreaticoenteric anastomosis is performed, DPG was associated with decreased CR-POPF incidence compared to DPJ. Future clinical trials are needed to confirm the generalizability of this result across centers with varying DPG expertise.